Understanding the rebound surface hardness of concrete - Szilágyi, Katalin; Borosnyói, Adorján; Zsigovics, István (Journal of Civil Engineering and Management, 2015)
Surface hardness testing of materials can be considered as the oldest method to get information about strength related material properties. In recent decades the rebound hammer has been the most popular surface hardness testing device for concrete uniting the advantages of its predecessors. In the technical literature numerous proposals are available for simple, two-parameter regression analyses of rebound surface hardness vs. compressive strength relationship of concrete. The remarkable diversity of the proposed curves implies the need of the more than two-parameter regression techniques to reveal the most pronounced parameters governing hardness behaviour. The objectives of present experimental studies were to carry out dynamic and static hardness tests, Young’s modulus and compressive strength tests on concrete specimens. From the development of the tested properties with time it can be concluded that the rebound hammers provide a hardness value for high strength concretes connected to the Young’s modulus rather than the compressive strength. Present paper includes a parametric simulation and a parameter fitting of the verified phenomenological constitutive model of the authors which recognizes the w/c ratio as the main driver of the interrelated material properties and gives a realistic formulation for the time dependent behaviour of the rebound surface hardness of concrete.